2005
DOI: 10.1161/01.res.0000182677.89816.38
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation in Angiotensin II–Induced Organ Damage

Abstract: Abstract-We tested whether or not complement activation participates in angiotensin (Ang) II-induced vasculopathy. We used double transgenic rats harboring human renin and angiotensinogen genes (dTGR) with or without losartan or the human renin inhibitor aliskiren. Sprague-Dawley (SD) rats were controls. DTGR had increased blood pressure at week 5 that increased further by week 7. Albuminuria was absent at week 5 but increased markedly in weeks 6 and 7. C-reactive protein (CRP) elevation, macrophages, T cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 34 publications
4
101
0
4
Order By: Relevance
“…Moreover, Ang I-forming capacity of the sera from these rats was also significantly reduced. A subsequent report by this group 72 showed that treatment with aliskiren inhibited complement activation and cellular infiltration in kidneys of dTGR. These studies showed the efficacy of aliskiren in high Ang II-induced renal injury and suggested a beneficial effect of the drug in complement-dependent renal disease.…”
Section: Testing Aliskiren In Animal Modelsmentioning
confidence: 89%
See 2 more Smart Citations
“…Moreover, Ang I-forming capacity of the sera from these rats was also significantly reduced. A subsequent report by this group 72 showed that treatment with aliskiren inhibited complement activation and cellular infiltration in kidneys of dTGR. These studies showed the efficacy of aliskiren in high Ang II-induced renal injury and suggested a beneficial effect of the drug in complement-dependent renal disease.…”
Section: Testing Aliskiren In Animal Modelsmentioning
confidence: 89%
“…In both the above studies, 71,72 AT 1 receptor blockers were included as positive controls; they were not intended to be comparator agents. These drugs were administered at different dosages and by different routes of administration than aliskiren.…”
Section: Testing Aliskiren In Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the RAAS can modulate the activation of complement system in both atherosclerosis and renal injury [53].…”
Section: Part II -Role Of the Renin-angiotensin-aldosterone System Onmentioning
confidence: 99%
“…Anti-TNFtherapy (Infliximab) has been demonstrated to lower both serum CRP and IL-6 levels in patients with a systemic inflammatory response [174]. Modification of the renin-angiotensin system may also reduce concentrations of both CRP and complement [175].…”
Section: Regulation Of Crpmentioning
confidence: 99%